Renewable water treatment adsorbent based on shale gas drilling oil base rock debris deoiling residues and preparation and regeneration methods thereof
By mixing the deoilation residue of shale gas drilling oil bedrock chips with sodium hydroxide and aluminum hydroxide, calcining and crystallization treatment, a renewable water treatment adsorbent is prepared and its regeneration method is provided, the existing technology is solved The problem of failure to effectively utilize the deoil residue has achieved efficient adsorption and recycling.
Patent Information
- Application Number
- CN202411664460.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art has failed to effectively utilize shale gas drilling oil bedrock deoiling residues, and its removal rate in water treatment has not been verified.
Renewable water treatment adsorbent is prepared by mixing the deoilation residue of shale gas drilling oil bedrock chips with sodium hydroxide and aluminum hydroxide, calcining and crystallization, and a renewable method is provided.
It has achieved efficient adsorption of ammonia nitrogen compounds and organic matter in water, reduced the emission of oil bedrock chips, and improved the recycling efficiency of adsorbents through regeneration methods.
Smart Images

Figure HDA0005144254940000011 
Figure HDA0005144254940000012 
Figure HDA0005144254940000013
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid waste resource utilization, and specifically to a renewable water treatment adsorbent based on shale gas drilling oil-based cuttings deoiling residue and a preparation and regeneration method thereof. Background Art
[0002] Shale gas drilling oil-based cuttings contain a lot of mineral oil and have been included in the "National List of Hazardous Wastes 2021 Edition". Pyrolysis is an important method for treating oil-based cuttings at home and abroad. After treatment, the remaining solid phase-oil-based cuttings deoiling residue is finally produced. However, since the oil-based cuttings deoiling residue may still have biological toxicity, its rational resource utilization has attracted widespread attention. At present, the main resource utilization of oil-based cuttings deoiling residue is mainly concentrated in the field of building materials utilization, mainly including cement kiln co-disposal, concrete preparation, brick making, roadbed material preparation, construction ceramsite preparation and other resource processing technologies. Although the oil-based cuttings deoiling residue can be disposed of as a building material, it is easily restricted by the development of the building materials industry, and the market value of the building material product as a resource is not high.
[0003] As a mineral rich in silicon and aluminum, shale gas drilling oil-based cuttings meet the chemical composition required for the preparation of zeolite molecular sieve adsorbents and can be used as a raw material for zeolite-like adsorbent materials. Using the deoiled residue of shale gas drilling oil-based cuttings to prepare adsorbent materials is one of the ways to convert and utilize them at a high value. The prior art CN201810011878.3 has demonstrated the feasibility of using shale gas oil-based drilling cuttings pyrolysis ash as raw material to prepare zeolite, and mentioned that the obtained artificial zeolite is suitable for the exchange treatment of ammonia nitrogen ions in sewage, however, it has not verified the removal rate of ammonia nitrogen ions by artificial zeolite.
[0004] Therefore, a new method for preparing renewable water treatment adsorbents is needed to fill the current technical gap in preparing renewable water treatment adsorbents based on deoiling residues. Summary of the invention
[0005] The problem that the present application aims to solve is to provide a renewable water treatment adsorbent based on shale gas drilling oil-based rock cuttings deoiling residue and a preparation and regeneration method thereof, so as to realize the resource utilization of the deoiling residue and be able to realize the recycling of the water treatment adsorbent while ensuring a high regeneration rate and a high adsorption rate.
[0006] In order to solve the above technical problems, this application adopts the following technical solutions:
[0007] In one aspect, the present application provides a method for preparing a renewable water treatment adsorbent based on shale gas drilling oil-based cuttings deoiling residue, comprising the following steps:
[0008] The de-oiled residue is first ground and sieved to obtain a de-oiled residue powder; the de-oiled residue powder is mixed with sodium hydroxide and aluminum hydroxide and then second ground to obtain a reaction system; the reaction system is roasted to obtain an alkali-melted product; deionized water is added to the alkali-melted product, stirred and then allowed to stand for stratification, and a precipitate is collected; and the precipitate is transferred to a reactor, crystallized, washed, filtered and dried to obtain the renewable water treatment adsorbent;
[0009] Wherein, the mass ratio of the deoiled residue powder to the sodium hydroxide is 1:(1.2-1.4);
[0010] The molar ratio of silicon to aluminum in the reaction system is (1-3):1;
[0011] The calcination temperature is 320-350°C, and the calcination time is 2-4h;
[0012] The crystallization temperature is 100-120° C., and the crystallization time is 3-24 hours.
[0013] Furthermore, the screening is carried out on a 100-mesh sieve.
[0014] Furthermore, the amount of the deionized water used is 1.2 to 1.4 times the sum of the mass of the de-oiled residue powder and the sodium hydroxide.
[0015] Furthermore, the washing is to wash the product obtained after the crystallization to neutrality.
[0016] In yet another aspect, the present application provides a renewable water treatment adsorbent obtained by the above preparation method.
[0017] In another aspect, the present application provides a renewable water treatment adsorbent prepared by the above method or a method for regenerating the above renewable water treatment adsorbent, comprising the following steps:
[0018] The used water treatment adsorbent is filtered, and then a NaCl solution is added to the solid obtained by the filtration to obtain an electrolyte; and the electrolyte is stirred on a constant temperature stirrer, and an electrode plate is placed in the electrolyte for electrolysis. After the electrolysis is completed, the electrolyte is filtered and heat-treated to obtain a regenerated water treatment adsorbent;
[0019] Wherein, the concentration of the NaCl solution is 0.001-0.0025 g / mL.
[0020] Furthermore, the stirring speed is 100-400 rpm r / mL, and the stirring temperature is 5-40°C.
[0021] Furthermore, the electrode plate is one of a BDD electrode and a titanium-based metal electrode.
[0022] Furthermore, the distance between the electrodes of the electrolysis is 2 cm, and the current density of the electrolysis is 300 to 500 A / m 2 The voltage of the electrolysis is 10 to 15 V, and the time of the electrolysis is 60 to 90 min.
[0023] Furthermore, the temperature of the heat treatment is 120-160°C.
[0024] This application has the following beneficial effects:
[0025] (1) When the preparation method provided by the present application utilizes the de-oiled residue of shale gas drilling oil-based cuttings to prepare a water treatment adsorbent, the calcination and crystallization temperatures are low and the reaction time is short, which greatly reduces energy consumption;
[0026] (2) The present application makes full use of the oil-based cuttings generated by shale gas drilling and converts them into non-toxic and harmless water treatment adsorbents with high market value, which can greatly reduce the discharge of oil-based cuttings;
[0027] (3) The water treatment adsorbent prepared in the present application can effectively adsorb ammonia nitrogen compounds and organic matter in water, achieving the effect of treating water pollution with solid waste and realizing the purpose of "treating waste with waste";
[0028] (4) After use, the water treatment adsorbent prepared in the present application can restore its adsorption capacity for ammonia nitrogen compounds and organic matter in water and maintain a high activity after electrochemical and thermal treatment, thereby realizing the recycling of the adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A process flow chart for preparing a water treatment adsorbent based on deoiled residues of shale gas drilling oil-based cuttings for this application;
[0030] Figure 2 The treatment effect of the water treatment adsorbent in Example 6 of the present application on simulated wastewater of different concentrations (A: ammonia nitrogen solution; B: methylene blue solution);
[0031] Figure 3 The treatment effect of the water treatment adsorbent in Example 7 of the present application on simulated wastewater of different pH values (A: ammonia nitrogen solution; B: methylene blue solution);
[0032] Figure 4 This is the simulated wastewater treatment effect of the water treatment adsorbent under different regeneration times in Example 8 of the present application (A: Experimental Group 1, B: Experimental Group 2; a and c: ammonia nitrogen solution, b and d: methylene blue solution). DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.
[0034] Example 1
[0035] The residue after de-oiling from shale gas drilling oil-based cuttings pyrolysis treatment was used as raw material, and the silicon and aluminum elements in the de-oiled residue were analyzed by XRF. The analysis results are shown in Table 1.
[0036] Table 1
[0037] element Si Al Element percentage (%) 28.331 8.6112
[0038] Example 2
[0039] Follow these steps to prepare the renewable water treatment adsorbent:
[0040] S11. The de-oiled residue in Example 1 was crushed and ground using a pulverizer, and the ground solid was placed in a 100-mesh sieve for sieving to obtain a de-oiled residue powder;
[0041] S12. Take 5 g of the deoiled residue powder, add 6 g of sodium hydroxide and mix, then add aluminum hydroxide to make the Si:Al in the mixture = 1:1, mix and grind using a mortar to obtain a reaction system;
[0042] S13. The reaction system was placed in a muffle furnace and calcined at 300 ° C for 2 h to obtain an alkali-melted product;
[0043] S14. 13.2 mL of deionized water was added to the alkali-melted product, stirred at room temperature for 3 h, allowed to stand for 30 min, and the precipitate was collected;
[0044] S15. The precipitate is transferred to a reactor, and after crystallization in an oven at 100°C for 3 hours, the crystallized product is washed with deionized water until it is neutral, and then filtered. The sample obtained by filtration is placed in an oven at 100°C and dried for 120 minutes to obtain the renewable water treatment adsorbent.
[0045] Example 3
[0046] Follow these steps to prepare the renewable water treatment adsorbent:
[0047] S11. The de-oiled residue in Example 1 was crushed and ground using a pulverizer, and the ground solid was placed in a 100-mesh sieve for sieving to obtain a de-oiled residue powder;
[0048] S12. Take 5 g of the deoiled residue powder, add 6.5 g of sodium hydroxide and mix, then add aluminum hydroxide to make the Si:Al in the mixture = 2:1, mix and grind using a mortar to obtain a reaction system;
[0049] S13. The reaction system was placed in a muffle furnace and calcined at 325 ° C for 3 h to obtain an alkali-melted product;
[0050] S14. Add 14.95 mL of deionized water to the alkali-melted product, stir at room temperature for 3 h, let stand for 30 min, and collect the precipitate;
[0051] S15. The precipitate is transferred to a reactor, and after crystallization in an oven at 110°C for 12 hours, the crystallized product is washed with deionized water until it is neutral, and then filtered. The sample obtained by filtration is placed in an oven at 100°C and dried for 120 minutes to obtain the renewable water treatment adsorbent.
[0052] Example 4
[0053] Follow these steps to prepare the renewable water treatment adsorbent:
[0054] S11. The de-oiled residue in Example 1 was crushed and ground using a pulverizer, and the ground solid was placed in a 100-mesh sieve for sieving to obtain a de-oiled residue powder;
[0055] S12. Take 5 g of the deoiled residue powder, add 7 g of sodium hydroxide and mix, then add aluminum hydroxide to make the Si:Al in the mixture = 3:1, mix and grind using a mortar to obtain a reaction system;
[0056] S13. The reaction system was placed in a muffle furnace and calcined at 350 ° C for 2h to obtain an alkali-melted product;
[0057] S14. 18.2 mL of deionized water was added to the alkali-melted product, stirred at room temperature for 3 h, allowed to stand for 30 min, and the precipitate was collected;
[0058] S15. The precipitate is transferred to a reactor, and after crystallization in an oven at 120° C. for 24 hours, the crystallized product is washed with deionized water until it is neutral, and then filtered. The sample obtained by filtration is placed in an oven at 100° C. and dried for 120 minutes to obtain the renewable water treatment adsorbent.
[0059] Example 5 Verification of the ammonia nitrogen removal effect of the renewable water treatment adsorbent
[0060] The renewable water treatment adsorbents prepared in Examples 2 to 4 were added to 100 mL of 100 mg / L NH4Cl solution at pH 7, respectively, and placed in a constant temperature oscillator at 25°C for 2 hours, and then centrifuged at a speed of 5000 r / min for 5 minutes. The supernatant was collected after centrifugation. The ammonia nitrogen concentration in the supernatant was determined by Nessler's reagent method, and the data measured by ultraviolet spectrophotometer are shown in Table 2.
[0061] Table 2:
[0062] project Ammonia nitrogen adsorption (mg / g) Removal rate (%) Example 2 5.7 57 Example 3 6.1 61 Example 4 6.6 66
[0063] According to Table 2, the present application uses the deoiled residue of shale gas drilling oil-based cuttings as raw material to prepare water treatment adsorbent. When the slag-alkali ratio is 1:1.4, the silicon-aluminum ratio is 3:1, the roasting temperature is 350°C, the amount of deionized water is 1.4 times that of the molten product, and the crystallization time is 24h, the obtained water treatment adsorbent has the best adsorption effect on ammonia nitrogen compounds in aqueous solution, reaching an adsorption capacity of 6.6 mg / g and a removal rate of 66%. The optimal water treatment adsorbent was selected for subsequent experiments.
[0064] Example 6 Determination of the removal effect of water treatment adsorbent on ammonia nitrogen compounds or organic matter of different concentrations
[0065] Take 1g of the water treatment adsorbent prepared in Example 4, add it to 100mL of ammonia nitrogen solution or methylene blue solution with concentrations of 50mg / L, 100mg / L, 200mg / L, 300mg / L, 350mg / L, and 400mg / L, respectively. The pH of the ammonia nitrogen solution and the methylene blue solution is adjusted to 7 in advance using hydrochloric acid or sodium hydroxide. Then put the ammonia nitrogen solution or methylene blue solution into a constant temperature oscillator at 25°C and oscillate and adsorb at a speed of 200r / min for 150min. After the adsorption is completed, the Nessler reagent method is used to measure and calculate the removal rate of ammonia nitrogen compounds, the methylene blue spectrophotometry method is used to measure and calculate the removal rate of methylene blue, and the ultraviolet spectrophotometer is used to determine the adsorption amount of ammonia nitrogen compounds or methylene blue by the water treatment agent adsorbent. The results are as follows: Figure 2 shown.
[0066] According to the results, it can be seen that the water treatment adsorbent prepared in Example 4 has an ammonia nitrogen removal rate of 60% to 69% in ammonia nitrogen solutions of different concentrations, and an adsorption capacity of 6.0 to 6.9 mg / g; the methylene blue removal rate in methylene blue solutions of different concentrations is 96% to 98%, and the adsorption capacity is 9.6 to 9.8 mg / g.
[0067] Example 7 Removal effect of water treatment adsorbents at different pH on ammonia nitrogen compounds or organic matter
[0068] Take 1g of the water treatment adsorbent prepared in Example 4, and add it to 100mL of ammonia nitrogen solution or methylene blue solution with a concentration of 100mg / L and a pH of 3, 4, 5, 6, 7, 8, 9, and 10, respectively. Then put the ammonia nitrogen solution or methylene blue solution into a constant temperature oscillator at 25°C and oscillate and adsorb at a speed of 200r / min for 150min. After the adsorption is completed, the Nessler reagent method is used to measure and calculate the removal rate of ammonia nitrogen compounds, the methylene blue spectrophotometry method is used to measure and calculate the removal rate of methylene blue, and the ultraviolet spectrophotometer is used to determine the adsorption amount of ammonia nitrogen compounds or methylene blue by the water treatment agent adsorbent. The results are as follows: Figure 3 shown.
[0069] According to the results, it can be seen that the water treatment adsorbent prepared in Example 4 has an ammonia nitrogen removal rate of 25% to 66% in ammonia nitrogen solutions with different pH values, and an adsorption capacity of 2.5 to 6.6 mg / g; the methylene blue removal rate in methylene blue solutions with different pH values is 92% to 99%, and the adsorption capacity is 9.2 to 9.9 mg / g.
[0070] Example 8 Regeneration efficiency of water treatment adsorbent and removal effect after regeneration
[0071] S21. Set up two groups of simulated wastewater, take 10mL of 1000mg / L ammonia nitrogen solution and methylene blue solution in each group of simulated wastewater, dilute to 100mL, and obtain simulated ammonia nitrogen wastewater and simulated methylene blue wastewater with a concentration of 100mg / L;
[0072] S22. Add 1g of the water treatment adsorbent prepared in Example 4 to the simulated ammonia nitrogen wastewater and the simulated methylene blue wastewater, respectively, and then place them in a constant temperature oscillator at 25°C for 150min of oscillation adsorption at a speed of 200r / min. After the adsorption is completed, use a vacuum pump to filter and collect the solid samples and filtrates of the simulated ammonia nitrogen wastewater and the simulated methylene blue wastewater in the two groups of simulated wastewater, respectively. The collected solid samples are placed in an oven for drying, and the filtrates are respectively determined by Nessler's reagent method and methylene blue spectrophotometry to calculate the removal rate of ammonia nitrogen compounds or methylene blue in the simulated wastewater;
[0073] S23. Divide the dried solid sample into two parts of equal weight, respectively as experimental group 1 and experimental group 2. Add 0.2g NaCl to experimental group 1 and 0.5g NaCl to experimental group 2, and then use deionized water to make the volume to 200mL. Place experimental group 1 in a constant temperature stirrer at 5℃ and stir at a speed of 400r / min. At the same time, put in a BDD electrode and energize for electrolysis. Set the current density of electrolysis to 500A / m 2, the voltage was 10-15V, the electrolysis was performed for 90min, and after the electrolysis was completed, the solid sample of experimental group 1 was filtered, and then the solid sample of experimental group 1 was heat treated at 120℃ for 2h; experimental group 2 was placed in a constant temperature stirrer at 40℃ and stirred at a speed of 100r / min, and a titanium-based metal electrode was placed and energized for electrolysis, and the current density of the electrolysis was set to 300A / m 2 , the voltage was 10-15V, the electrolysis was performed for 60min, and after the electrolysis was completed, the solid sample of the experimental group 2 was subjected to heat treatment at 160℃ for 2h, and the electrolyte solid samples of the experimental group 1 and the experimental group 2 were collected respectively.
[0074] S24. The electrolyte solid sample was subjected to four repeated adsorption and regeneration experiments;
[0075] S25. Collect and record the removal rates of simulated ammonia nitrogen wastewater and simulated methylene blue wastewater and the regeneration efficiency of water treatment adsorbents for 5 times. The results are as follows: Figure 4 shown.
[0076] According to the results, it can be seen that in experimental group 1 and experimental group 2, the treatment capacity of the water treatment adsorbent for ammonia nitrogen wastewater or methylene blue wastewater did not change much. Among them, the removal rate of ammonia nitrogen compounds in ammonia nitrogen wastewater of experimental group 1 decreased from 68% to 58%, an overall decrease of 10%, and the regeneration efficiency was 85%, and the removal rate of methylene blue in methylene blue wastewater decreased from 98% to 85%, an overall decrease of 13%, and the regeneration efficiency was 86%; the removal rate of ammonia nitrogen compounds in ammonia nitrogen wastewater of experimental group 2 decreased from 68% to 60%, an overall decrease of 8%, and the regeneration efficiency was 88%, and the removal rate of methylene blue in methylene blue wastewater decreased from 98% to 85%, an overall decrease of 13%, and the regeneration efficiency was 86%.
[0077] In summary, the method provided in the present application can convert the de-oiled residue into a water treatment adsorbent with use value at a lower temperature. The obtained water treatment adsorbent has excellent removal effects of ammonia nitrogen compounds and organic matter, and realizes the waste utilization of the de-oiled residue. The once regenerated adsorbent obtained by the regeneration method provided in the present application has a water treatment effect that is not much different from that of a new adsorbent, and after multiple regenerations, it can still ensure that the adsorption effect and regeneration efficiency of the water treatment adsorbent remain at a high level.
[0078] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a renewable water treatment adsorbent based on deoiling residues of shale gas drilling oil-based cuttings, characterized in that: The following steps are involved: The deoiled residue is first ground and sieved to obtain a deoiled residue powder; The deoiled residue powder is mixed with sodium hydroxide and aluminum hydroxide and then subjected to a second grinding to obtain a reaction system; calcining the reaction system to obtain an alkali-melted product; Add deionized water to the alkali-melted product, stir, let stand to separate, and collect the precipitate; as well as The precipitate is transferred to a reactor for crystallization, washing, suction filtration and drying to obtain the renewable water treatment adsorbent; Wherein, the mass ratio of the deoiled residue powder to the sodium hydroxide is 1:(1.2-1.4); The molar ratio of silicon to aluminum in the reaction system is (1-3):1; The calcination temperature is 300-350°C, and the calcination time is 2-4h; The crystallization temperature is 100-120° C., and the crystallization time is 3-24 hours.
2. The preparation method according to claim 1, characterized in that: The sieving is performed using a 100-mesh sieve.
3. The preparation method according to claim 1, characterized in that: The amount of the deionized water used is 1.2 to 1.4 times the sum of the mass of the de-oiled residue powder and the sodium hydroxide.
4. The preparation method according to claim 1, characterized in that: The washing is to wash the product obtained after the crystallization to neutrality.
5. A renewable water treatment adsorbent obtained by the preparation method according to any one of claims 1 to 4.
6. The renewable water treatment adsorbent prepared by the method according to any one of claims 1 to 4 or the method for regenerating the renewable water treatment adsorbent according to claim 5, characterized in that: The following steps are involved: The used water treatment adsorbent is filtered, and then a NaCl solution is added to the solid obtained by the filtration to obtain an electrolyte; and The electrolyte is stirred on a thermostatic stirrer, and an electrode plate is placed therein for electrolysis, and after the electrolysis is completed, the electrolyte is filtered and heat treated to obtain a regenerated water treatment adsorbent; Wherein, the concentration of the NaCl solution is 0.001-0.0025 g / mL.
7. The regeneration method according to claim 6, characterized in that: The stirring speed is 100-400 rpm, and the stirring temperature is 5-40°C.
8. The regeneration method according to claim 6, characterized in that: The electrode plate is one of a BDD electrode and a titanium-based metal electrode.
9. The regeneration method according to claim 6, characterized in that: The distance between the electrodes of the electrolysis is 2 cm, and the current density of the electrolysis is 300-500 A / m 2 The voltage of the electrolysis is 10 to 15 V, and the time of the electrolysis is 60 to 90 min.
10. The regeneration method according to claim 6, characterized in that: The temperature of the heat treatment is 120-160°C.
Citation Information
Patent Citations
Preparation method and products of zeolite from oil-based drill cuttings pyrolysis ash
CN108046284B
Ammonia adsorbent regeneration and regeneration liquid pollution-free disposal method and device
CN101862646A
Method for preparing zeolite by taking oil-based drilling pyrolytic ash as raw material, and product
CN108046284A
Method for preparing heavy metal cadmium adsorption fixing agent from oil shale ash and fly ash
CN111013527A
Continuously adsorbing-electrolyzing regenerated wastewater treating apparatus
CN1201759A